IMPLEMENTASI KEBIJAKAN PENYALURAN HIBAH DAN BANTUAN SOSIAL PADA BAGIAN ADMINISTRASI KESEJAHTERAAN RAKYAT DAN KEMASYARAKATAN DAERAH KABUPATEN PONOROGO JAWA TIMUR - ERVIANA, NORA (Dinamika Hukum, 2019)
The distribution of grants and community social stones is in accordance with the applicable procedures and provisions, but in the field there are several proposals that come in and receive instructions from the Regent to be assisted, so the solution is disbursed through direct shopping. Dissemination of grant programs and social assistance is still not optimal, there is still overlap in the distribution of aid, designated organizations have less role in carrying out their duties, there is still nepotism in the provision of grants and social assistance. A prospect appeared that was not verified by the relevant institution, many beneficiaries did not verify the data. Keywords: Implementation, Grant Distribution Policy and Social Assistance